Plasma Protein Oxidation Is Associated with an Increase of Procoagulant Markers Causing an Imbalance between Pro- and Anticoagulant Pathways in Healthy Subjects - De Cristofaro, Raimondo; Rocca, Bianca; Marchioli, Roberto; Landolfi, Raffaele (Thrombosis and Haemostasis, 2002)
The aim of the present study was to investigate whether the overall oxidation state of plasma proteins is associated with changes of circulating pro- and anticoagulant markers in healthy subjects (n = 99, 49 males, 50 females, aged from 6 to 91 yrs.). The carbonyl content of plasma proteins was measured and validated as an ex vivo index of the overall protein oxidation state due to its correlation with the plasma level of o-tyrosine (r = 0.87, P <0.0001), which is a well known oxidized product of L-phenylalanine. Using a multivariate analysis the carbonyl content of plasma protein was positively associated with procoagulant markers such as prothrombin F1 + 2 (r = 0.28, P = 0.0019) and fibrinopeptide A, (FpA) (r = 0.278, P = 0.003), as well as with the soluble derivative of the endothelial protein thrombomodulin (TM) (r = 0.469, P <0.0001). The procoagulant marker of thrombin activity, FpA, was significantly and positively correlated with the anticoagulant product of thrombin, namely the Protein C activation peptide (PCP), only in the tertile with low protein carbonyl content. At higher tertiles this correlation was no longer observed, thus suggesting a detrimental effect of oxidative stress on the TM/Protein C anticoagulant pathway. In 15 subjects with high carbonyl content of plasma protein, treatment for 18 days with 600 mg/d of vitamin E did not substantially modify the protein carbonyl content, the anticoagulant markers APC/PCP, and all procoagulant markers except F1+2, whose value significantly decreased by 25%.In conclusion, the present study shows that a high plasma protein oxidation ex vivo is associated with an overall hemostatic imbalance, which favors procoagulant markers. Vitamin E treatment in vivo restores only in part the equilibrium between pro- and anticoagulant pathways. This may open the way to further studies aimed at elucidating the mechanisms by which the oxidative stress is linked to activation of the coagulation system in atherothrombotic disorders.Abbreviations: APC: activated Protein C; F1+2: prothrombin fragment 1+2; FpA: fibrinopeptide A; PCP: Protein C activation peptide; TM: thrombomodulin
Keywords: Protein oxidation; coagulation pathways; antioxidant agents